2017
DOI: 10.1177/1179547617698460
|View full text |Cite
|
Sign up to set email alerts
|

Clot in Lung, Clot in Heart: A Case Report of Tumor-Like Thrombus in Right Atrium

Abstract: Tumor-like formation of thrombus in the right atrial cavity is rare. It may be mistaken for a myxoma. The exact pathophysiology of an isolated thrombus in the heart is still unclear. Management to prevent complications such as pulmonary thromboembolism depends on the clinical judgment of a cardiologist. This report describes a 76-year-old woman with right atrial thrombus causing subsequent pulmonary thromboembolism in right lung. She initially presented to us with pulmonary embolism, and later, an incidental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Invasive cardiac intervention might be a possible cause since Habibi R et al reported a patient with a right atrial pacemaker lead insertion developed a similar right atrial thrombus. [ 11 ] Our patient had not received any invasive cardiac interventions before, but he did have 1 possible risk factor for thrombus formation. It was the medical history of right femoral neck fracture, which might gave rise to deep vein thrombus in lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive cardiac intervention might be a possible cause since Habibi R et al reported a patient with a right atrial pacemaker lead insertion developed a similar right atrial thrombus. [ 11 ] Our patient had not received any invasive cardiac interventions before, but he did have 1 possible risk factor for thrombus formation. It was the medical history of right femoral neck fracture, which might gave rise to deep vein thrombus in lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial thrombi are more often located in the left atrium or appendage and are generally accompanied by structural heart disease[ 23 ]. They are usually highly mobile, serpiginous and without the typical myxoma features[ 24 , 25 ] such as the attachment via a stalk and the presence of intramass calcification[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…After anticoagulation treatment, the right atrial mass was smaller than before, which verified the diagnosis of right atrial thrombosis. A total of 5 cases of myxoma-like right atrial thrombosis in the past 10 years from 2011 to 2021 were screened out through PubMed, including 4 elderly patients and 1 young patient, showing different symptoms such as palpitations, dyspnea and syncope (7)(8)(9)(10)(11). All patients had thromboembolic causes of cardiac thrombosis, including cardiac structural abnormalities, catheter-related thrombosis, pacemaker implantation, and longterm bed rest history.…”
Section: Discussionmentioning
confidence: 99%